Central liponeurocytoma as a clinical entity - (:unkn) unknown (ELSEVIER URBAN & PARTNER SP Z O O, 2018)
Introduction: Liponeurocytomas are mostly localized in cerebellar hemispheres and the second most common location is the vermis. It is rarely observed within the intracranial ventricles. Here, we present a case of liponeurocytoma located in the right lateral ventricle and the systematic review of the literature. State of the art: We searched PubMed with keyword 'central liponeurocytoma' and the references of the related articles. There were no language or year restrictions. We included articles focusing on liponeurocytomas located in the central nervous system leaving a total of 17 articles and 21 reported cases Clinical implications: A 62-year-old female presented with confusion and mental disorientation without any other neurological deficit. Her magnetic resonance imaging (MRI) revealed a lateral ventricle located mass lesion which was hypointense on T1-weighted images (WI) and heterogeneously hyperintense on T2-WI with cystic component. Via craniotomy, yellow-beige colored, soft and moderately vascularized mass lesion was gross totally resected. Despite postoperative MRI revealed total resection, patient had left-sided hemiparesis. The patient recovered well in her postoperative period and there was no recurrence on her 6th month follow-up MRI. Future directions: Intraventricular liponeurocytoma has a favorable clinical course, and radiological features may be useful in the diagnosis of this rare tumor before surgery. Supratentorial intraventricular location should be kept in mind in the differential diagnosis of the lateral ventricular tumors. (C) 2018 Polish Neurological Society. Published by Elsevier Sp. z o.o. All rights reserved.
Keywords: Liponeurocytoma; Lateral ventricle; Supratentorial; CENTRAL-NERVOUS-SYSTEM; CEREBELLAR LIPONEUROCYTOMA; MEDULLOBLASTOMA; CLASSIFICATION; TUMORS; NEUROCYTOMA; ADULTS